Main Pulmonary Artery Stump Thrombosis After Fontan Completion: Anatomic Predisposition, Clinical Impact, and Management - Eun Chae Kim; Woong-Han Kim; Jae Gun Kwak (Pediatric Cardiology, 2026)
Abstract Thrombosis arising from a main pulmonary artery (MPA) stump or related blind pouch remains a potentially devastating but under-recognized complication in patients after the Fontan operation. We aimed to evaluate the contemporary clinical characteristics, management strategies, and outcomes of patients with MPA stump–related pathology. We retrospectively reviewed patients treated between 2003 and 2023 who either developed MPA stump thrombosis after Fontan completion or underwent pulmonary valve obliteration for MPA stump–related problems. Nine patients were identified, including three previously reported cases and six newly identified patients. Clinical characteristics, imaging findings, management strategies, and long-term outcomes were analyzed. MPA stump pathology was diagnosed at a median age of 18.2 (15.5–29.3) years, occurring a median of 15.9 (14.5–28.7) years after MPA ligation. Thrombus size ranged from 8 × 6 mm to 37 × 17 mm, and supraventricular arrhythmia was present in seven patients at diagnosis. Three patients experienced systemic thromboembolic events, including cerebral and renal infarction. Seven patients underwent surgical intervention, whereas two were managed conservatively. During a median follow-up of 14.6 (4.5–19) years after treatment for MPA thrombus, no recurrent thromboembolic events or deaths occurred. MPA stump–related pathology can cause late systemic thromboembolism after Fontan completion. Both overt thrombosis and severe blood stasis represent high-risk substrates, and surgical elimination of the MPA stump may represent a potential preventive strategy. These findings represent a hypothesis-generating observation supporting future evaluation of proactive strategies such as concomitant pulmonary valve obliteration at the time of MPA ligation.